Hungarian Monitoring, 23 October 1990 . [Magyar rádiófigyelő], 1990. október 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Hussein tries to win Paris over for himself - Balkan foreign ministers' conference in Tirana Domestic Affairs: - Lithuanian president attends commemorations - First anniversary of the Republic of Hungary - World meeting of freedom fighters in the Sports Hall - Warsaw Pact November meeting postponed - Memorial plaque for armed forces members who fell in 1956 removed by force from Hungarian Radio building Külpolitika: - Husszein igyekszik megnyerni Párizst magának - A Balkán külügyminisztereinek tanácskozása Tiranában Belpolitika: - Megemlékezések a litván elnök részvételével - Egyéves a Magyar Köztársaság - Szabadságharcos világtalálkozó a Sportcsarnokban - Elhalasztják a VSZ novemberi ülését - A rádió épületéről leverik az elesett karhatalmisták emléktábláját